Butterfly communities in miombo woodland: Biodiversity declines with increasing woodland utilisation. (December 2015) - Jew, Eleanor K.K.; Loos, Jacqueline; Dougill, Andrew J.; Sallu, Susannah M.; Benton, Tim G.
ABSTRACT: Deforestation and degradation are threatening forests and woodlands globally. The deciduous miombo woodlands of sub-Saharan Africa are no exception, yet little is known about the flora and fauna they contain and the implications of their loss. Butterflies are recognised as indicators of environmental change; however the responses of butterflies in miombo woodlands have received little attention. This paper describes butterfly assemblages and their response to woodland utilisation in an understudied area of miombo woodland in south-west Tanzania. This is an area representative of miombo woodlands throughout sub-Saharan Africa, where woodland is utilised by local communities for a range of products, and is being rapidly converted to agriculture. Baited canopy traps and sweep nets were used to sample frugivorous and nectarivorous butterfly communities at different vertical stratifications in nine different study sites. 104 species were recorded, of which 16 are miombo specialists that have been recorded in Tanzania to the west of the country only. Indicator species were identified for three different levels of utilisation, with species from the sub-family Satyrinae indicating moderate utilisation. Generalised linear mixed effects models showed that butterfly species richness, diversity and abundance all decreased in response to increasing agriculture and anthropogenic utilisation. The loss of miombo woodlands is likely to result in declines in butterfly diversity. However, there was evidence of an intermediate disturbance effect for butterfly species richness, diversity and abundance with one utilisation variable, suggesting that a miombo woodland management plan that allows moderate sustainable utilisation in a heterogeneous landscape of mature miombo woodland and agriculture will simultaneously maintain butterfly communities and enable agricultural production. Highlights: Butterflies were surveyed in miombo woodland along a gradient of utilisation. 16 species are miombo specialists and only occur in Tanzania to the west of the country. Frugivorous butterflies responded to more utilisation variables than nectarivores. Diversity, richness and abundance showed a unimodal relation to utilisation. Managing a mixed miombo and agriculture system would maintain butterfly communities.